The Nazi and the psychiatrist : Hermann Goring, Dr. Douglas M. Kelley, and a fatal meeting of minds at the end of WWII - El-Hai, Jack (PublicAffairs, 2014)
Ace reportage on the unique relationship between a prison physician and one of the Third Reich's highest ranking officials.